THE LEGAL PROTECTION FOR REAL LAND RIGHT HOLDER IN CASE OF FORGED RINCIK - Nirwana, Nirwana; Patittingi, Farida; Nur, Sri Susyanti (Tadulako University, 2017)
The legal Protection For Real Land Right Holder in Case of Forged Rincik. The research aimed to investigate (1) the legal protection for the land owner whose possession was based on rincik evidence, and (2) the legal protection on the good-will buyer based on the forged rincik document used in the land sale transaction. This was the normative legal research, also called the library research or documentary study because the research was only conducted on the written regulations or other legal materials or secondary data consisting of the primary and secondary legal materials. The interview was performed to strengthen the theories and opinions in the research. The research also used the Secondary data. the data were analysed and presented using the qualitative descriptive method. The research result indicate that: (1) the real land owner with rincik possession issued after the year 1960 based on the decision of Indonesian Supreme Court No. 560K / PID / 2008 has not been fully protected due to the fact that the seller is funished for forging the rincik., returning the right to the land owner can not be carried out due to the decision of Indonesian Supreme Court Number. 482 / PK / Pdt / 2014 which make the buyer win, while the real land owner is the directed to sue the land seller to give the compensation: and (2) the legal protection on the good faith buyer based on forget rincik in the land sale transaction has been fully protected and has the ringt to possess the land based on the decision of Indonesian Supreme Court Number. 482/PK/Pdt/2014 because the buyer has bought the land in the presence of Temporary Land Title Registar.